Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 1 - Limits and Their Properties - 1.5 Exercises: 21


Vertical asymptote at $x=0$ or $x=3$

Work Step by Step

$f(x)=\dfrac{4x^2+4x-24}{x^4-2x^3-9x^2+18x}=\dfrac{4(x+3)(x-2)}{x(x-2)(x+3)(x-3)}$ $=\dfrac{4}{x(x-3)}.$ Vertical asymptotes occur when the denominator alone is $0\to$ $x(x-3)=0\to x=0$ or $x=3.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.